1993
DOI: 10.1111/j.1439-0523.1993.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity for RFLPs in European Maize Inbreds

Abstract: Restrictionfragment length polymorphisms (RFLPs) have been proposed for predicting the yield potential of different types of cross. Their has been evaluated in 15 flint and 12 dent inbreds from the European maize {Zea mays L.) germplasm as well as in 68 F, crosses (21 flint X flint, 14 dent X dent, and 33 flint X dent) produced between them. The materials were evaluated for Fi performance and midparent heterosis of grain yield, dry matter content (DMC) and plant height in two environments in Germany. Genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…[2 ] expressed doubt on the usefulness of increased genome coverage with additional markers for increasing the correlations between marker distance and hybrid performance to improve the efficiency of the prediction. They alternatively suggested identification of marker loci and genotypes significantly associated with traits of interest.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[2 ] expressed doubt on the usefulness of increased genome coverage with additional markers for increasing the correlations between marker distance and hybrid performance to improve the efficiency of the prediction. They alternatively suggested identification of marker loci and genotypes significantly associated with traits of interest.…”
Section: Discussionmentioning
confidence: 97%
“…Whereas the results of Melchinger et aI. [9] and Boppenmaier et al [2] indicated that the correlations between marker distance and F1 performance are dependent on the origin of lines studied; the correlations are high for crosses between lines from the same heterotic groups, low between lines from different heterotic groups, and intermediate for mixtures consisting of lines both within and between groups. Despite the inconsistency in the correlations, results from all these studies indicate that genetic distances based on marker genotypes are in close agreement with pedigree information and can unambiguously resolve lines into their respective heterotic groups.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, the association of genetic distance with heterosis in elite inbred lines of corn may be very strong (Lee et al, 1989;Smith et al, 1990) or weak (Godshalk et al, 1990;Dudley et al, 1991), because the correlation between marker distance and F 1 performance depends on the origin of lines studied (Melchinger et al, 1990;Boppenmaier et al, 1993). Genetic background plays an important role in heterosis.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of heterotic groups has played a great role in the development of inbred lines and hybrids in maize (Boppenmaier et al, 1993;Dubreuil et al, 1996). lnbreds can be classified according to their origin from different landraces and/or the contributions from their main ancestors (Smith et al, 1990).…”
Section: Introductionmentioning
confidence: 99%